1995
DOI: 10.1007/bf02188775
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcome of operative treatment for lumbar spinal stenosis

Abstract: 96 patients with lumbar spinal stenosis were operated on after two to sixteen years of disabling symptoms. There were 50 women and 46 men with a mean age of 59 years. 33 of the patients had been previously operated on for spinal complaints. A laminectomy was performed in 61 patients; at one level in 31 patients, at two levels in 23 patients, and at three levels in seven patients. A hemilaminectomy was performed in 35 patients: at one level in 28 patients, at two levels in five patients, and at three levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 10 publications
0
37
1
Order By: Relevance
“…In several studies, there appeared to be a tendency toward poorer results for smokers, but this difference was not statistically significant. 18,50,[97][98][99][100] Although the surgical results were inferior for smokers in our study, it should be emphasised that even the smokers experienced considerable pain reduction and improvement in their QoL and walking ability after decompressive surgery. Consequently, our study should not be used as an argument to encourage smokers not to undergo surgery for spinal stenosis on an individual level.…”
Section: Effect Of Smoking On Surgical Resultscontrasting
confidence: 61%
“…In several studies, there appeared to be a tendency toward poorer results for smokers, but this difference was not statistically significant. 18,50,[97][98][99][100] Although the surgical results were inferior for smokers in our study, it should be emphasised that even the smokers experienced considerable pain reduction and improvement in their QoL and walking ability after decompressive surgery. Consequently, our study should not be used as an argument to encourage smokers not to undergo surgery for spinal stenosis on an individual level.…”
Section: Effect Of Smoking On Surgical Resultscontrasting
confidence: 61%
“…Several investigations have shown that the results of lumbar spine surgery are also adversely affected by cigarette-smoking, with lower rates of fusion, poorer clinical outcomes, and higher rates of postoperative infection in smokers [4][5][6][7][8][9][10][11] . Initially, it was postulated that the lower rate of consolidation of posterolateral lumbar spinal grafts among smokers was due to a lower oxygen-carrying capacity of the bloodstream 4 .…”
mentioning
confidence: 99%
“…In addition, the prevalence of degenerative conditions such as spinal stenosis, arthritis of the intervertebral disc or facet joints, and spinal deformities increase as a patient ages, potentially creating a conundrum of increased rates of pathology in patients who are at higher risk for treatment. 1,2,7,8,11 Indeed, in a recent review of Medicare claims data for 2002-2007, the rate of complex fusion procedures increased from 1.3 to 19.9 per 100,000 beneficiaries.…”
mentioning
confidence: 99%